Viability of lymphocyte culture, at different times after blood collection, for karyotype analysis - Ligia Maria Crubelati Bulla; Eliane Papa Ambrosio; Ana Beatriz Tozzo Martins; Valter Augusto DellaRosa (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction:Cytogenetics is the area of genetics that studies chromosomes, including numerical changes, and their relationship to structural imbalances. Among the classical cytogenetics tests, the GTG banding karyotype is the most widely used. The period of culture establishment is a critical step, which can affect the pre-analytical phase of the test.Objective:To evaluate, at different establishment times, culture viability and banding resolution.Material and methods:Collection of 10 ml blood from 10 subjects was carried out for culture analysis. For viability analysis, mitotic index (MI) and banding resolution were assessed. Results: The comparative analysis of MI showed significant difference between times. In the assessment of banding resolution, the mean value of the bands was higher at times zero and 24 hour.Discussion:The MI reflects inhibition of cell cycle progression and/or loss of ability to proliferate. When the pair analysis was performed, a difference between zero and 48 hours was observed. The average number of bands analyzed at times zero and 24 hours did not indicate difference in the quantity and quality of the bands when cultures were grown immediately after blood collection or within 24 hours. At the 48th hour after blood collection significant reduction of band resolution was observed.Conclusion:These data highlight the importance of the biological material quality, as viability is lower when the culture is grown after 24 hours, as well as the banding resolution.